Upscaling Corporate Governance Principles for Performance of National Sports Federations in Kenya and Beyond - Mumani, Mical Oluteyo; Muathe, Stephen Makau (European Scientific Journal, ESJ, 2025)
The sports industry in Kenya continues to grow swiftly and emerge as a vibrant and crowd-pulling phenomenon. However, few studies have been conducted on the critical topic of corporate governance principles and the performance of national sports federations. Thus, the research focused on determining the effect of corporate governance principles on National Sports Federations’ performance in Nairobi City County, Kenya. The objectives included evaluating the effects of transparency, accountability, sustainability, and integrity on National Sports Federations’ performance in Nairobi City County, Kenya. The study variables were anchored in the Stewardship theory, Balanced Scorecard theory, and Stakeholder theory. The research utilized both secondary and primary data. The research utilized a descriptive research design to collect data from a sample of 145 federation members: Head of National Team Coaches, Assistant National Team Coaches, and Technical Directors. Semi-structured questionnaires were utilized for data collection. Self-administered Questionnaires were utilized, employing the drop-off and later pick-up approach. Data was analyzed using the Statistical Package for Social Sciences (SPSS). Quantitative data collected was analyzed using multiple regression, descriptive analysis, and Correlation analysis. The study found that accountability, transparency, integrity, and sustainability have a significant positive relationship with the performance of national sports federations in Nairobi City County. Further findings reveal that increased service delivery, customer feedback, employee satisfaction, and financial performance of national sports federations indicate performance. This study recommends the formation of clear corporate governance policies that raise sustainable development in the Kenya sporting sector, federation members to adopt continuous training on best practices of corporate governance, utilize digital platforms for governance practices, national and county government to establish measurable performance indicators to be adopted by national sports federations, consistent monitoring, and evaluation of these performance indicators. These recommendations will help both the national sports federations and the government to increase transparency, accountability, sustainability, and integrity in the sports industry in Kenya.